Digital Pilkada: Have Local Elections (Pilkada) been Affected by Digitalization? Attainment, Challenges, and Policy Solutions - Saksono, Herie (Jurnal Bina Praja, 2020)
The advancement of digital technology forces humans to make adjustments in all aspects of life, likewise, with the local elections' holding (Pilkada). However, the conditions for each region in the Indonesian archipelago have different problems. Availability of telecommunication facilities, local elections (Pilkada) organizers, level of difficulty in Frontier, Outermost, and Disadvantaged Region (3T), community digital literacy level, and accuracy of results. Have the local elections (Pilkada) been digitalized? How far has it been achieved? What challenges are faced, and what are the solutions? Several studies on e-voting, even the local elections (Pilkada) digitization, have been carried out. This study is novel because it looks at the 2020 local elections (Pilkada) implementation from digitalization that was carried out in line with the COVID-19 pandemic. Due to data limitations and availability, this study only focuses on implementing local elections (Pilkada) in nine provinces. This study uses a qualitative method based on a literature review with a systematic review method. The study aims to reveal the achievements and challenges of digitalization in the implementation of local elections (Pilkada) along with policy solutions so that digitalization is more completed. Through analysis, it was found that the organizers of the local elections (Pilkada) have made efforts to realize digitalization. Various Subscriber Identity Modules (SIM) and applications have been created by the General Election Commission (KPU), the General Election Supervisory Board (Bawaslu), and the General Election Organizer Honorary Council (DKPP). It is hoped that digitalization will further increase the effectiveness, efficiency, and quality of service. Besides, the data shows that there are obstacles in the field, especially the availability of telecommunication infrastructure, which is very diverse in the nine provinces. Fundamentally, it is necessary to formulate regulations/policies that synergize the implementation of local elections (Pilkada) through the adoption of digital technology based on the internet of things (IoT), big data analysis, and artificial intelligence (AI). The local elections (Pilkada) digitization brings several benefits - more transparent, accountable, credible, practical, and economical. On the other hand, the community feels more of its services because the digital local elections (Pilkada) procession educates the public to elect local leaders with integrity.